Dosimetric study of hypo fractionated adjuvant post mastectomy radiotherapy with and without bolus and assessment of acute toxicity of treatment: a single institution study - Sidhu, Majinder S.; Sood, Sandhya; Aggarwal, Ritu; Singh, Kulbir (International Journal of Research in Medical Sciences, 2021)
Background: Moderate hypo fractionated PMRT is convenient for patients and is particularly beneficial in busy radiotherapy department like in developing nations. Furthermore, PMRT can be given with or without bolus as per institution protocol. The purpose of this study was to do dosimetric comparison of with and without bolus plans in patient undergoing hypo fractionated PMRT and to assess acute toxicity of treatment. Methods: Our study is single institution prospective study done at DMCH cancer center Ludhiana, Punjab, India. Study period was from March 2020 to October 2020 and we included post mastectomy patients irradiated by hypo fractionated regime. After CT simulation and contouring, rapid arc radiotherapy plans were evaluated and DVH analysis was done for PTV and OARs. Acute toxicity was assessed during treatment and 1 month post radiotherapy treatment. Ethical approval was not taken due to COVID 19 pandemic emergency, but also hypofractionated PMRT is standard of care. Statistical analysis was done on SPSS, Version 20.0 Results: A total of 30 patients were analyzed which received mean PTV dose of 42.3Gy in 16 fractions (8 fractions with and 8 without bolus).We were able to achieve adequate PTV coverage in plan sum which included both bolus and non-bolus plan. However, use of bolus resulted in statistically significant increase in low dose volume mainly V4Gy of ipsilateral lung in left sided breast cancer cases. Despite use of bolus no patient had above grade I skin toxicity. Conclusions: Moderate hypo fractionated PMRT with and without bolus is well tolerated with minimal acute side effects. It is important to note that use of bolus results in higher V4Gy volume of ipsilateral lung more precisely in left side breast cancer cases.